Enhanced Reality and Intraoperative Imaging in Colorectal Surgery - Ris, Frederic; Yeung, Trevor; Hompes, Roel; Mortensen, Neil J. (Clinics in Colon and Rectal Surgery, 2015)
Colorectal surgery is one of the most common procedures performed around the world with more than 600,000 operations each year in the United States, and more than a million worldwide. In the past two decades, there has been a clear trend toward minimal access and surgeons have embraced this evolution. Widespread adoption of advanced minimally invasive procedures is often limited by procedural complexity and the need for specific technical skills. Furthermore, the loss of 3D vision, limited overview of the surgical field, and diminished tactile sensation make major colorectal procedures more challenging and have an impact on the surgeons' learning curves. New technologies are emerging that can compensate for some of the sensory losses associated with laparoscopy. High-definition picture acquisition, 3D camera systems, and the use of biomarkers will allow improved identification of the target structures and help differentiate them from surrounding tissues. In this article, we describe some of the new technologies available and, in particular, focus on the possible implications of biomarkers and fluorescent laparoscopic imaging.
Keywords: laparoscopic colorectal cancer resection; colorectal surgery; biomarkers; indocyanine green; enhanced reality; imaging